Requirements for shifting from item budgets to program and performance budgets in Palestinian government institutions : An applied study on the Ministry of Health in the Gaza Strip (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The current study aims to assess the availability of the requirements for shifting to the program and performance budgeting system at the Palestinian Ministry of Health - Gaza Strip. The researcher used the descriptive analytical method. A structured self-administered questionnaire was used within the current study. This questionnaire was primarily based on the theoretical framework of the current study and the available literature.The study population included 84 participants. Those participants were all employees holding financial supervisory titles as well as the executive employees working in the General Department of Financial Affairs at the Ministry of Health. A total of 71 participants responded to the study with 84.5% response rate. SPSS statistical software was used (version 20).The study revealed the availability of several requirements that are necessary to shift from traditional budgeting to the program and performance budgeting system. To a high extent, the hierarchical requirements, legislative and administrative regulations are largely met within the ministry of health. To an intermediate extent, human resource knowledge and technical capacities, the computer-based infrastructure, software, in addition to the accounting and financing system capacities were met.The study recommended for the ministry of Finance, particularly the General directorate of Budgeting, to develop detailed procedural guidelines, the components of the accounting system, the financial policies, the procedural system of cost accounting, the responsibility accounting, and the transition to the accrual basis concept.